Adolescentes em tempo integral: vivências - saberes - significados : a construção da identidade de adolescentes a partir de vivências em projetos de educação em tempo integral na Rede Municipal de Educação Belo Horizonte - Catherine Monique de Souza Hermont (2008)
This research seeks to understand the meanings attributed by adolescents to experience on a proposal for extension of school time. Seeking to understand the formation of identities and young learners The study was conducted in a school in the municipal system of education of Belo Horizonte and its surroundings / community. Two classes that were the Project Network of the 3rd cycle, a total of 56 students from 12 to 17 years. The collection of data, qualitative approach, was performed in three steps: starting the monitoring of students during the 2nd half of 2006, in an ethnographic perspective. During the year 2007, were semi-structured interviews with participants of the class with different trajectories, data were collected on the path to the school setting such interviews. Finalizing the data collection, there were some group discussions at the end of 2007, based on photos and materials collected during the monitoring of the class. Allowing register some information on the progression of school students. Data analysis allowed to understand the meanings spend all day at school and the concepts of self constructed. The relationship between these two identities are formed from different concepts of being young and being students, and are presented in different ways. Three areas of expertise to articulate for the construction of these concepts: school experiences of previous years, the year 2006 in time "regular" cycle and the 3rd time in "extended" the project. Understood to be young and be pupil / student is not achievable task for all participants of the group studied.